Analisis Kemampuan Peserta Didik Menyelesaikan Soal Ujian Nasional Terpilih dari Tahun 2016-2018 Mata Pelajaran IPA Bidang Fisika di SMP Negeri Kecamatan Batauga - Tina, Wa; Sahara, La; Sukariasih, Luh (Universitas Halu Oleo, 2021)
This study aims (1) to find out the picture of students ability to complete the questions of the selected National Examination from 2016-2018 science subjects in physics at Batauga District Junior High School, (2) to determine the ability of students to complete selected National Examination questions from 2016-2018 science subjects in physics at Batauga District Junior High School in terms of the scope of the subject matter, and (3) to determine the ability of students to complete selected National Examination questions from 2016-2018 science subjects in physics at Batauga District Junior High School in terms of the sola multiple choice. This type of research is descriptive research. The population in this study were all class IX learners enrolled in the 2018/2019 school year at the State Junior High School in Batauga Distrid. Data collection techniques using the test of the National Examination in science subjects. Data analysis techniques in this study by making tabulation of data in the from of scores, determining the value of students, calculating the number of class interval values, determining the average and standard deviations, analyzing the percentage of students answer and grouping the results of analysis based on the percentage of students answers. Based on the results of research and discussion conclusions are obtained: (1) the ability of students in completing the questions of the National Examination selected from 2016-2018 natural science subjects in physics at Batauga Distrid Junior High School, the average value obtained students by 52,0, (2) the ability of students in completing the questions of the National Examination selected from 2016-2018 science subjects in physics at Batauga District Junior High School based on the highest scope of the subject matter that is the scope of measurement matter, substances and properties with and average value of 56,9, and the lowest is the scope of the matter waves, electricity and magnetism with and average value of 46,4, and (3) the ability of students to completing selected National Examination questions from 2016-2018 natural science subjects in physics at Batauga District Junior High School based on the highest multiple choice from that is the multiple choice associations with an average value of 59,9 and the lowest is the multiple choice image/graph/table with an average value of 50,5.